Sincerity and Devotion-Based Education: (Case Study at Al-Ishlah Lamongan Islamic Boarding School) - Muhammad Arwani Rofi'i; Nazilatul Fatihah Firdaus; Emilia Rachmawati (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This research provides valuable insight into the implementation of Education based on sincerity and service in Islamic educational institutions, especially the Al-Ishlah Lamongan Islamic Boarding School, as well as a basis for further understanding of the contribution of this Education to the formation of qualified and empowered individuals. The qualitative research method used involves observation, interviews, and documentary studies to understand the educational approach at Al-Ishlah Islamic Boarding School. Various data collection techniques are used to gather accurate information. The research results show that Education at this Islamic boarding school is based on the principle of sincerity, where every educational activity is based on a sincere intention to seek Allah's approval. Apart from that, the concept of devotion is aimed at God, others, and society. Al-Ishlah Lamongan Islamic Boarding School not only aims to convey religious knowledge but also to shape its students into empowered individuals with noble character and social awareness. Education based on sincerity and devotion at the Al-Ishlah Lamongan Islamic Boarding School provides a positive contribution to character formation and student empowerment in the context of Islamic Education. Education based on sincerity and dedication at Al-Ishlah Islamic Boarding School in Lamongan has several significant implications: 1) Character Development: Students are taught to be sincere and serve sincerely, improving their character. 2) Improvement of Education Quality: Focus on sincerity and dedication enhances education quality. 3) and others.